Histoenzymiatic and Histochemical studies on proventiculus and gizzard of male love birds (Psittacula cuvier) (Indian Journal of Animal Production and Management, 2025)
This study was designed to investigate the histoenzymatic and histochemical study of stomach in male love birds (Psittacula Cuvier). The study was performed on five male birds . the results were demonstrated that the mucoal epithelium in proventriculus was reacted with (ALP) positively but the reaction was not found in sub- mucosa , Tunica muscularis and serosa, also the results were showed that the mucosal epithelium and glands of proventriculus was reacted with (AB 2.5) on the other hand our results were revealed that the distribtion of (ALP) in gizzard was moderate in mucosal epithelium and aweak in koilin layer wherease the reaction was positively in koilin layer with (AB 2.5).
Keywords: designed; investigate; histoenzymatic; histochemical